Machado de Assis: representação literária do fim do Império - Leonel, Maria Célia [UNESP]; Segatto, José Antonio [UNESP] (Universidade Estadual Paulista (Unesp), 2009)
Propõe-se o exame das relações entre determinados recursos literários de Esaú e Jacó e Memorial de Aires e elementos sociopolíticos e históricos da transição do Império para a República representados nesses romances machadianos. Pretendemos mostrar como, por meio de escolhas estruturais e linguísticas, no que se refere aos vínculos entre narrador, focalização e personagens, o escritor traz à baila questões substantivas da sociedade brasileira daquele momento. Ao contrário do que alguns analistas apontam, há, nessas narrativas, crítica às relações sociais e de poder. A forma como o escritor realiza, nos romances, a refl exão sobre tais relações enseja novas pesquisas.

Our purpose is to examine the relations between certain literary procedures used in Esau and Jacob and Counselor Ayres’ Memorial (also translated as The Wager: Aires’ Journal), and socio-political and historical elements present in the transition from the Empire to the Republic, both represented in these two novels by Machado de Assis. We aim to show how – by means of structural and linguistic choices concerning the bonds between narrator, focalization and characters – the writer brings into discussion important subjects of the Brazilian society at that moment. Contrary to what is pointed out by some critics, there is a critique of the social and power relations in these narratives. The way in which the writer conducts his reflection on these relations gives rise to new researches.
Machado de Assis: literary representation of the end of Brazil's second empire period
Keywords: Fiction; History; Politics; Machado de Assis; Narrator; Ficção; História; Política; Narrador